The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1470595820973438
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of the Leadership Effectiveness in Africa and the Diaspora (LEAD) scale

Abstract: This article contributes to the literature on cross-cultural leadership by describing the development and validation of the Leadership Effectiveness in Africa and the Diaspora (LEAD) Scale. The LEAD Scale is a culturally sensitive measure of leadership effectiveness in the understudied settings of Africa and the African diaspora. A combination of methods and four studies using samples from Africa and the African diaspora based in Canada, the USA, and the Caribbean were used to develop the measure. Using the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Other approaches at this stage reported in literature included: 1) Delphi technique by Michaud et al [ 43 ] in their item generation stage, where participants were asked to discuss and rate different concepts of interest, 2) Benschop et al [ 44 ] when designing a new tool for understanding new psychoactive substance use in six European countries, conducted extensive literature-based review, country reports and expert consultation to understand the policy and context of substance use, which informed their item generation, 3) O’Brien et al [ 31 ] also reported that their research team had members with diverse culture, different ages and experiences which helped to reduce biases.…”
Section: Resultsmentioning
confidence: 99%
“…Other approaches at this stage reported in literature included: 1) Delphi technique by Michaud et al [ 43 ] in their item generation stage, where participants were asked to discuss and rate different concepts of interest, 2) Benschop et al [ 44 ] when designing a new tool for understanding new psychoactive substance use in six European countries, conducted extensive literature-based review, country reports and expert consultation to understand the policy and context of substance use, which informed their item generation, 3) O’Brien et al [ 31 ] also reported that their research team had members with diverse culture, different ages and experiences which helped to reduce biases.…”
Section: Resultsmentioning
confidence: 99%
“…We do not present details of the research project, because our intent is simply to use this project to illustrate the proposed emic-etic-emic cycle, which provides deeper understanding of the context in under-researched countries (refer to Figure 1). A more complete discussion of the development of the survey instrument can be found in (Michaud, Lvina, Galperin, et al, 2020).
Figure 1.Model of iterative research process.
…”
Section: Putting An Emic-etic-emic Cycle Into Practice: the Lead Projectmentioning
confidence: 99%
“…Additionally, Pillai and Williams (1998); Lone and Lone (2018) remarked that leadership effectiveness consists of three dimensions, namely developing followership, achieving results, and team playing. According to Michaud et al (2020), leadership effectiveness has three main variables that are very influential, namely the nature of the task, the relationship between leaders and subordinates, and the power inherent in the position of leader. From the previous literature, effective leadership can be concluded as an activity in forming interactions to influence others through a systematic mindset, effective in decision making and communicating the results of thought (Kurucay & Inan, 2017;Huguet, 2017).…”
Section: Irje |Indonesian Research Journal In Education| |Vol 5| No 2...mentioning
confidence: 99%
“…Leadership effectiveness is the achievement of leaders in completing one or several tasks, and leadership effectiveness can also be seen from the satisfaction obtained by the followers (Gibson et al, 2016). Additionally, Michaud et al (2020) revealed that the effectiveness of leadership has three namely the nature of the task (what must be done), the relationship between leaders and subordinates, and the power inherent in the position of leader.…”
Section: Leadership Effectiveness and Work Motivationmentioning
confidence: 99%